PENERAPAN SIMPLE ADDITIVE WEIGHTING AND LOCATION QUOTIENT UNTUK MENENTUKAN LOKASI PENYEBARAN TERNAK (Studi Kasus : Kabupaten Brebes) - Anggraini Kusumaningrum (Institut Teknologi Dirgantara Adisutjipto, 2013)
The government self-sufficiency program about Cattle and Buffalo have not been success, because the distributed of livestock is not according with the regulation. It is only used the ecological factor and have not used the other factor like human resource and institutional factor, technology and the development of the region factor, development of infrastructure. This research have been modeling with Multi Criteria Decision Making (MCDM). Simple additive weighting (SAW) is one method of MCDM, it used for decide the suitability of location and the result of SAW support by Location Quotient (LQ) for allocation priority of livestock in the region. The result of this research is the combination of methods SAW and LQ could be implementation and give the right alternative based on priority allocation for the decision maker to allocation the livestock.